INDONESIA’S AIR SOVEREIGNTY ISSUES IN THE GLOBAL ERA - Adya Paramita Prabandari (Fakultas Hukum, Universitas Diponegoro, 2019)
A state has a government as the supreme authority that has a complete and exclusive jurisdiction over its territory. It is very important to Indonesia, with its vast territory, to preserve and uphold the state’s sovereignty, particularly over its airspace. Especially in this global era, when the rapid development of technologies resulting in the end of geography era, and the world seems to be borderless. The issue discussed in this paper is Indonesia’s air sovereignty issues in the global era. The things to be concerned by the Government of Indonesia on the management and protection of the state’s sovereignty over the airspace in the global era are: (1) the take over of the Flight Information Region above Riau and Natuna from Singapore FIR; (2) the prevention and suppression of airspace violation incidents; and (3) the impact of Indonesia’s ratification on the ASEAN Open Skies Policy to the protection of the sovereignty over Indonesia’s airspace. A state’s airspace is very strategic because it is the first fortress of a state, in which all foreign forces can fly in first. Therefore as a state with vast territory, the Government of Indonesia must work hard to be able to preserve and uphold the sovereignty over its territory, especially in defending the state’s sovereignty over its airspace in the global era.